Mitochondrial Neurogastrointestinal Encephalomyopathy: Into the Fourth Decade, What We Have Learned So Far - Pacitti, Dario; Levene, Michelle; Garone, Caterina; Nirmalananthan, Niranjanan; Bax, Bridget E. (Frontiers in Genetics, 2018)
Mitochondrial neurogastrointestinal encephalomyopathy (MNGIE) is an ultra-rare metabolic autosomal recessive disease, caused by mutations in the nuclear gene TYMP which encodes the enzyme thymidine phosphorylase. The resulting enzyme deficiency leads to a systemic accumulation of the deoxyribonucleosides thymidine and deoxyuridine, and ultimately mitochondrial failure due to a progressive acquisition of secondary mitochondrial DNA (mtDNA) mutations and mtDNA depletion. Clinically, MNGIE is characterized by gastrointestinal and neurological manifestations, including cachexia, gastrointestinal dysmotility, peripheral neuropathy, leukoencephalopathy, ophthalmoplegia and ptosis. The disease is progressively degenerative and leads to death at an average age of 37.6 years. As with the vast majority of rare diseases, patients with MNGIE face a number of unmet needs related to diagnostic delays, a lack of approved therapies, and non-specific clinical management. We provide here a comprehensive collation of the available knowledge of MNGIE since the disease was first described 42 years ago. This review includes symptomatology, diagnostic procedures and hurdles, in vitro and in vivo disease models that have enhanced our understanding of the disease pathology, and finally experimental therapeutic approaches under development. The ultimate aim of this review is to increase clinical awareness of MNGIE, thereby reducing diagnostic delay and improving patient access to putative treatments under investigation.